Biomechanics & Sports Orthopedics - Jelkmann W (Dynamic Media Sales Verlag, 2020)
The present articleprovides an overview on the significance of autologous red blood cell (RBC) transfusion (ABT) in the hospital and its misuse in sports. Such overview seems timely given several ABT doping scandals. ABTs can avoid harms caused by allogeneic blood transfusions (e.g. blood-borne diseases and immunosuppression) and save blood resources.Still, in clinical practice ABT has fallen into disuse. Due to the loss of hemoglobin (Hb), blood donation acutely impairs physical fitness. In particular, the loss of iron is critical. It takes 20 days to 2 months for full Hb mass restoration after a ~550 mL phlebotomy (1-unit). RBC concentrates are prepared by the removal of plasma and leukocytes, and maintained in plasticized polyvinyl chloride bags. There are two techniques for RBC storage: refrigeration (cold storage) or freezing (cryopreservation). In the clinical setting, cold-stored RBCs must be re-infused after 42 days, due to increasing storage lesions, whereas cryopreservation allows for storage for up to 30 years. RBC transfusions can enhance performance. Illegal ABT with cryopreserved RBCs appears to be a method of choice in doping athletes, because no valid laboratory method exists to prove such event. WADAs hematological Athlete Biological Passport (ABP) has provided some progress. In addition, Report Doping platforms for whistleblowers have been established.KEY WORDS: Anemia, Athlete Biological Passport, Hemoglobin, Doping, Cryopreservation